To answer this question we will use the following slope-point formula for the equation of a line:
![y-y_1=m(x-x_1)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/50rdws8olj8e9mrccwea6tp7o8rrt3xm71.png)
Recall that f'(x) is the slope of the tangent line to the graph at (x,f(x)).
Therefore, the tangent line of y=f(x) at x=2 has a slope of -4 and passes through (-2,-7).
Then, using the slope-point formula for the equation of a line we get:
![y-(-7)=-4(x-(-2))\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/f4mgodxsy34idp0w4ttzwivhw0lyt5kurf.png)
Simplifying the above result we get:
![\begin{gathered} y+7=-4(x+2), \\ y+7=-4x-8. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eu3i847rzbwor60562c1l8qrhc50xed1xb.png)
Subtracting 7 from the above equation we get:
![\begin{gathered} y+7-7=-4x-8-7, \\ y=-4x-15. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ef5t6yecqi7xzjpqxyb5wx5v82hqsghi2y.png)
Answer:
![y=-4x-15.](https://img.qammunity.org/2023/formulas/mathematics/college/40u0zfmppzh59jozruro045ngpgrqb25pt.png)